Sensitivity analysis of melting heat transfer in Williamson fluid - Aliya Batool; Zakir Hussain; Dilawar Hussain (Case Studies in Thermal Engineering)
The purpose of this study is to disclose the prominent parameters in Williamson fluid flow subject to melting heat transfer, modified porous medium and thermal radiation. A mathematical model has been formulated under conservative laws. The model is simplified to ordinary differential equations by introducing similarity variables and tackled by bvp4c Matlab function. The significant variables on flow model are identified by Response Surface Method (RSM). Analysis of variance (ANOVA) is employed to measure the relationship against flow variables for wall shear stress (Cf) and heat transfer (Nu). The empirical models formulated for Cf and Nu show 99.98% and 98.05% accuracy respectively. Sensitivity analysis is carried for inertia coefficient (0≤Fr∗≤3), melting parameter 0≤M≤3 and thermal radiation (0≤Rd≤3) against Cf and Nu. Further, the sensitivity explores that Fr∗ has more dominant effect on Cf when compared to M and Rd. Moreover, M has the most significant impact on Nu, Fr∗ and Rd.